An Analysis of Book T'alimul Muta'alim on Education Character and It’s Relationship with Education Character Programs at Indonesia - Bela, Nurita; Jannah, Siti Raudlatul; Jaenullah, Jaenullah (Bulletin of Pedagogical Research, 2023)
The article analyzed the values of education character that contained in the book Ta'limul Muta'allim by Al-Zarnuji, especially (1) reveal and identify the exposure of character education in the book Ta'limul Muta'allim, (2) describe the relevance of the values of character education in the book Ta'limul Muta'allim with character education in Indonesia. This type of research was qualitative research. This research uses the method of literature study, library research (library research). The primary data source is the Ta'limul Muta'allim book. Data collection techniques are carried out and processed with documentation in the form of writing, pictures, or monumental works from someone. The results of this study indicate that: (1) the values of character education in the book of Ta'limul Muta'allim include: active in learning, honest, intelligent, increasing knowledge, avoiding mutual hostility, choosing friends, humility, deliberation, loving nature, patient and persevering. (2) The relevance of the value of character education in the book Ta'limul Muta'allim with the value of character education in Indonesia contains the cultivation of values which include religious character, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, spirit of nationalism, love for the homeland, respect for achievements, friendly/communicative, love peace, love to read, care for the environment, care about social, and responsibility Keywords: Education Character, Education Character Program, Analysis T'alimul Muta'alim